Pengaruh Pupuk Kotoran Sapi dan Plant Growth Promoting Rhizobacteria pada Produksi Tanaman Buncis - Anggi Bimantara Andharesta; Sundahri Sundahri (Jurnal Ilmu Pertanian Indonesia, 2024)
The productivity of common beans has fluctuated in the last 5 years. The decrease and increase in productivity occur due to decreased soil quality due to a lack of organic matter. Plant productivity with excessive use of inorganic fertilizers can reduce soil fertility. The solution to restoring microbial activity and soil fertility levels can be taken through a nature farming approach, namely by utilizing organic fertilizers derived from cow manure and additional plant growth-promoting rhizobacteria (PGPR) biological fertilizers. This research was conducted at a production site on Jalan Tidar, Jember, East Java, from January to March 2023. The design used was factorial RAK with 3 repetitions. The first factor was the dose of cow manure, which consists of 4 levels, namely 0, 10, 15, and 20 tons/ha. The second factor was the concentration of PGPR, which consists of 4 levels: 0, 10, 15, and 20 mL/L. The results do not show any interaction between cow manure and PGPR on all parameters. Cow manure has a noticeable effect on growth parameters and quantity. The best dose of cow manure and the highest protein content value was 20 tons/ha. The concentration of PGPR had only a noticeable effect on plant height and number of leaves. PGPR concentrations of 15 mL/L and 20 mL/L both give the best results and produce the highest antioxidant activity value at 15 mL/L. Keywords: Antioxidant activity, common bean, cow manure, pgpr, protein